Mortality Influenced Factors for Outcome of Epidural Hematoma Patient Which Performed Emergency Craniotomy in M Djamil Hospital Padang Periode January-December 2017 - Amrizal Amrizal; Syaiful Saanin (Fakultas Kedokteran, Universitas Andalas, 2018)
Epidural Hematoma (EDH) is the most common emergency case in neurosurgery, mortality rate was higher than other country. To determine the factors that influence outcome of EDH patients with performed emergency craniotomy. This descriptive analytic was conducted at Dr. M. Djamil General Hospital, Padang, Indonesia, we review the medical record all of EDH patient in 2017. Some parameters were analyzed in our study, ages (p = 0.012), gender (p = 0.418), inisial GCS (p = 0.146), pupil abnormality (p = 0.973), onset (p = 0.883) and time delayedfor surgery (p = 0.146), the mortality rate was 7/26 patients. Age has a significant difference on the outcome of EDH patients who underwent emergency craniotomy. Whereas gender, initial GCS, pupil abnormality, onset trauma, delayed time are determinat factors that influence outcome but not significant.